Exploring the social responsibility of tabloid journalism in South Africa: Views from the Daily Sun and Sunday Sun - Mokwena, Dimakatso David (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.